Modifikasi Struktur Akseptor Zat Warna Tipe D-π-A Berbasis Ditiofen sebagai Sensitizer pada Sel Surya - Reshiva Reshiva; Imelda Imelda; Syukri Syukri; Admi Admi; Elvira Deswita (Jurnal Fisika Unand, 2025)
This study aims to evaluate the effect of variations in the acceptor group of dithiophen-based type D-π-A dyes that are efficiently used as sensitizers in DSSC. The calculation uses the 16W Gaussian program with Density Functional Theory (DFT) and Time Dependent-DFT (TD-DFT) methods with the B3LYP/6-31G set base. Based on the results of the study, it is known that acceptor variations can affect the shift in absorption spectrum and bandgap values. The dye AT5 is predicted to have higher efficiency to be used as a sensitizer, because it has the smallest bandgap value and has a dipole moment value, as well as a larger wavelength. The smaller the bandgap value, the absorbedyu light will shift towards the red shift, and the electron excitation process will be easier. It can be concluded that dyes with cyanide formal acceptors can improve the efficiency of D-π-A type dyes as sensitizers in DSSC.